Sun-Tanning Perceptions of a New Zealand Urban Population (1994-2005/6) - McGee, R.; Gray, Andrew; McLeod, G. F. H.; Reeder, A. I. (Journal of Skin Cancer, 2014)
Background. Sun-tanning perceptions are monitored to identify changes and help refine targeting of skin cancer prevention messages. Aim. To investigate associations between perceptions of sun-tanning and demographic factors among a New Zealand urban population, 1994–2006. Methods. A telephone survey series was conducted during summer in 1994, 1997, 1999/2000, 2002/2003, and 2005/2006. Demographic and personal information (sex, age group, skin sun-sensitivity, and self-defined ethnicity) obtained from 6,195 respondents, 50.2% female, 15–69 years, was investigated in relation to six sun-tanning related statements. A total “positive perceptions of tanning” (ProTan) score was also calculated. Regression analyses modelled each component and the ProTan score against survey year and respondent characteristics. Results. Statistically significantly higher ProTan scores were found for age group (strong reverse dose-response effect), male sex, residence (highest in Auckland), ethnicity (highest among Europeans), and sun sensitivity (an n -shaped association). There was no statistically significant change in total ProTan scores from baseline. Conclusions. The development, pretesting, and evaluation of messages for those groups most likely to endorse ProTan statements should be considered for the New Zealand skin cancer prevention program. To achieve and embed significant change, mass media campaigns may require greater intensity and reinforcement with sustained contextual support for settings-based behavioural change.